Effects of Intravenous Infusion of Lidocaine on Short-Term Outcomes and Survival in Patients Undergoing Surgery for Ovarian Cancer: A Retrospective Propensity Score Matching Study - Zhang, Hao; Gu, Jiahui; Qu, Mengdi; Sun, Zhirong; Huang, Qihong; Cata, Juan P.; Chen, Wankun; Miao, Changhong (Frontiers in Oncology, 2022)
Abstract Background: Intravenous lidocaine has been shown to reduce opioid consumption and is associated with favourable outcomes after surgery. In this study, we explored whether intraoperative lidocaine reduces intraoperative opioid use and length of stay (LOS) and improves long-term survival after primary debulking surgery for ovarian cancer and explored the correlation between SCN9A expression and ovarian cancer prognosis. Methods: This retrospective study included patients who underwent primary debulking surgery(PDS) for ovarian cancer from January 2015 to December 2018. The patients were divided into non-lidocaine[continuous bolus injection of 1.5 mg/kg saline at the induction of anaesthesia followed by a continuous infusion of 2 mg/(kg∙h) intraoperatively] and lidocaine [bolus injection of 1.5 mg/kg lidocaine at the induction of anaesthesia followed by a continuous infusion of 2 mg/(kg∙h) intraoperatively] groups. Intraoperative opioid consumption, the verbal numeric rating scale (VNRS) at rest and LOS were recorded. Propensity score matching was used to minimize bias, and disease-free survival (DFS) and overall survival (OS) were compared between the two groups. Results: After propensity score matching(PSM), the demographics were not significantly different between the groups. The intraoperative sufentanil consumption in the lidocaine group was significantly lower than that in the non-lidocaine group (Mean: 35.6 μg vs. 43.2 μg, P=0.035). LOS was similar between the groups (12.0 days vs. 12.4 days, P=0.386). There was a significant difference in DFS between the groups (32.3% vs. 21.6%, P=0.015), and OS rates were significantly higher in the lidocaine group than in the non-lidocaine group (35.2% vs. 25.6%, P=0.042). Multivariate analysis indicated that intraoperative lidocaine infusion was associated with prolonged OS and DFS. Conclusion: Intraoperative intravenous lidocaine infusion appears to be associated with improved OS and DFS in patients undergoing primary debulking surgery for ovarian cancer. Our study has the limitations of a retrospective review. Hence, our results should be confirmed by a prospective randomized controlled trial.